Provisional Agenda for the Thirty-First Meeting of the IMFC. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
The following is the provisional agenda for the Thirty-First Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on April 17, 2015.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet